2012
DOI: 10.2478/v10078-012-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Motor Variability, Accuracy, and Ball Speed in the Tennis Serve

Abstract: The main objective of this study was to analyze the motor variability in the performance of the tennis serve and its relationship to performance outcome. Seventeen male tennis players took part in the research, and they performed 20 serves. Linear and non-linear variability during the hand movement was measured by 3D Motion Tracking. Ball speed was recorded with a sports radar gun and the ball bounces were video recorded to calculate accuracy. The results showed a relationship between the amount of variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…This theoretical approach has been accepted by many researchers that have studied tennis movements, to bridge the gap between theoretical knowledge and the practice involved in training and during a match [6,7]. Girard et al [8] analyzed the kinematic of first tennis serve, while constraining the knee flexion angle, while Menayo et al [9] changed the type and size of the tennis racket and ball to assess the same movement. Nevertheless, although task constraints are usually easy to manipulate by coaches and researchers, the manipulation of environmental constraints is still a challenge [4].…”
Section: Introductionmentioning
confidence: 99%
“…This theoretical approach has been accepted by many researchers that have studied tennis movements, to bridge the gap between theoretical knowledge and the practice involved in training and during a match [6,7]. Girard et al [8] analyzed the kinematic of first tennis serve, while constraining the knee flexion angle, while Menayo et al [9] changed the type and size of the tennis racket and ball to assess the same movement. Nevertheless, although task constraints are usually easy to manipulate by coaches and researchers, the manipulation of environmental constraints is still a challenge [4].…”
Section: Introductionmentioning
confidence: 99%
“…as found in a study onanalysis of the volleyball "set shot found a pushing pattern, with players put their arms behind the ball to "push" in the direction of the ball trajectory, causing the ball to follow a more vertical arc, which was associated with greater accuracy" (Portus, 2011) (Tant, 1993)This shows that the skills, whose performance is throwing or pushing, are more aaccurate, compared to the beating skills (touch only),In the closed skills, greater mastery of performance Such as (tennis, table tennis, badminton, etc. ), (Antunez, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studies conducted on tennis players have shown that muscular strength has a significant effect on the effectiveness of service together with various rotational variables of the upper-extremity joints. When the close relation of muscular strength with body structure is considered, the importance of anthropometric and somatotype features in tennis becomes to the forefront (Antunez et al, 2012).…”
Section: Introductionmentioning
confidence: 99%